2020
DOI: 10.1021/acs.orglett.0c00312
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed C–H Acetoxylation of Phenols with Removable Monodentate Directing Groups: Access to Pyrocatechol Derivatives

Abstract: An efficient cobalt-catalyzed C–H acetoxylation of phenols has been developed by using PIDA (phenyliodine diacetate) as a sole acetoxy source to synthesize pyrocatechol derivatives for the first time. The key feature of this method is the use of earth-abundant metal cobalt as the green and inexpensive catalyst for the acetoxylation of C­(sp2)–H bonds under neutral reaction conditions. Furthermore, the gram-scale reaction and late-stage functionalization demonstrated the usefulness of this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Chelated cobalt(II) catalysts, such as [Co(acac) 2 ], can also be used in C-H activation methods to modify 2-phenoxypyridines, from which other biological activities can be discovered. Although they present a lower oxidation state, they are also powerful catalysts, as described by Gou, Cao, and co-workers for a C-H acetoxylation of phenol derivatives (Scheme 43B) [205]. In the presence of phenyliodine(III) diacetate (PIDA) the reaction leads to several ortho-directed acetoxylated products in moderate to good yields (Scheme 41C).…”
Section: Cobalt-catalyzed C-h Activationmentioning
confidence: 98%
See 1 more Smart Citation
“…Chelated cobalt(II) catalysts, such as [Co(acac) 2 ], can also be used in C-H activation methods to modify 2-phenoxypyridines, from which other biological activities can be discovered. Although they present a lower oxidation state, they are also powerful catalysts, as described by Gou, Cao, and co-workers for a C-H acetoxylation of phenol derivatives (Scheme 43B) [205]. In the presence of phenyliodine(III) diacetate (PIDA) the reaction leads to several ortho-directed acetoxylated products in moderate to good yields (Scheme 41C).…”
Section: Cobalt-catalyzed C-h Activationmentioning
confidence: 98%
“…In this work, a nickel-based metalorganic framework (MOF-74-Ni) mediated a C-H arylation process of several azole derivatives (Scheme 64A). The desired arylated products were obtained in good yields, including compounds known to present important biological activities (Scheme 64B and C) such as the caffeine derivative from 203 [289], texamine (204) [290], balsoxin (205) [290], and the previously mentioned uguenenazole (194) [276].…”
Section: Nickel-catalyzed C-h Activationmentioning
confidence: 99%
“…In 2020, Gou et al reported the first example of cobalt-catalyzed CÀ H acetoxylation of phenol derivatives (Scheme 14). [48] In their study, they used a pyridine directing group, which is easy to remove after targeted functionalization. [49] This cobalt catalysis features greener acetoxylation owing to the combinatorial use of phenyliodine diacetate (PIDA) as a single acetoxy source and oxygen as a non-toxic oxidant.…”
Section: Cà H Acetoxylationmentioning
confidence: 99%
“…What’s more, among these numerous elegant procedures reported in the literature, the directing group-free ortho -C–H difluoromethylation of aromatic rings to access difluorooxindoles, which are effectively accomplished by using 3d metal catalysis alone, also remains scarce. Furthermore, although nickel has high catalyst flexibility and chemical versatility for most molecular skeletons, previous attempts at nickel-catalyzed selective C–H difluoromethylation of aromatic rings have consistently failed so far. Herein, on the basis of our previous understanding of 3d metals, we develop a new and inexpensive catalytic system to vanquish the regioselectivity and sustainability of C–H difluoromethylation of aromatic rings (Figure c).…”
mentioning
confidence: 99%